Angle Class II, subdivision, with agenesis of mandibular second molars and extrusion of maxillary second molars - Rubens Rodrigues Tavares (Dental Press Editora, 2015)
This clinical case reports the treatment of an Angle Class II malocclusion in a young woman with a balanced face affected by agenesis of second and third mandibular molars and subsequent extrusion of second maxillary molars. The atypical and peculiar occlusal anomaly led to individualized treatment proposed in order to normalize dental malpositions, with subsequent rehabilitation of edentulous areas by means of a multidisciplinary approach. This case was presented to the Brazilian Board of Orthodontics and Dentofacial Orthopedics (BBO) in partial fulfillment of the requirements for obtaining the title of certified by the BBO.